Uncommon Location of Common Parasite (Nepalese Journal of Radiology, 2014)
Neurocysticercosis is the most common parasitic infection of the Central Nervous System caused by Taenia solium. Spinal cysticercosis is an uncommon site of cysticercal infestation & intramedullary involvement is even rarer.1 We are reporting a rare case of intramedullary cysticercosis in the cervical region in an 11 year old girl who presented with headache & neck stiffness. CT and MRI of the cervical spine done revealed a cystic lesion with mural nodule (scolex) with cord edema in the cervical region. The child underwent treatment with antihelminthic drugs and showed marked clinico-radiological improvement.DOI: http://dx.doi.org/10.3126/njr.v4i1.11373 Nepalese Journal of Radiology, Vol.4(1) 2014: 63-66